Human Colon-Derived Soluble Factors Modulate Gut Microbiota Composition - Hevia, Arancha; Bernardo, David; Montalvillo, Enrique; Al-Hassi, Hafid O.; Fernández-Salazar, Luis; Garrote, Jose A.; Milani, Christian; Ventura, Marco; Arranz, Eduardo; Knight, Stella C.; Margolles, Abelardo; Sánchez, Borja (Frontiers in Oncology, 2015)
The commensal microbiota modulates immunological and metabolic aspects of the intestinal mucosa contributing to development of human gut diseases including inflammatory bowel disease. The host/microbiota interaction often referred to as a crosstalk, mainly focuses on the effect of the microbiota on the host neglecting effects that the host could elicit on the commensals. Colonic microenvironments from three human healthy controls (obtained from the proximal and distal colon, both in resting conditions and after immune –IL-15- and microbiota –LPS- in vitro challenges) were used to condition a stable fecal population. Subsequent 16S rRNA gene based analyses were performed to study the effect induced by the host on the microbiota composition and function. Non-supervised Principal Component Analysis (PCA) showed that all microbiotas which had been conditioned with colonic microenvironments clustered together in terms of relative microbial composition, suggesting that soluble factors were modulating a stable fecal population. Our findings confirmed that the host intestinal microenvironment has the capacity to modulate the gut microbiota composition via yet unidentified soluble factors. These findings indicate that an appropriate understanding of the factors of the host mucosal microenvironment affecting microbiota composition and function could improve therapeutic manipulation of the microbiota composition.